Revolusi Mental dan Injil Kerajaan Allah - Jadi Sampurna Lima (Reformed Center for Religion and Society, 2022)
This article explains the gospel of Jesus Christ, which plays a crucial role in the “mental revolution”. This goal is achieved through analysing power relations, viewed from three contexts: first-century Judea, Dutch colonial Indonesia, and present-day Indonesia. The analysis focuses on the power dynamics between “the little people”, “the priayi”, and their Dutch masters, followed by a comparison to the history of oppression in first-century Judean society and the work of Jesus Nazareth and his disciples in producing a “mental revolution from below”. This research hopefully will guide how the gospel lived by Christians can orient their struggles as Indonesian citizens from the bottom of their hearts as citizens of the “kingdom of God”. The article tries to show how the Gospels convey a picture of Jesus Christ. He presented new habituation in his interactions with power and the marginalised in the corrupted first-century Judean society. This paper also explains how these findings can help Christians to work as modern Indonesian citizens.